Letter from J. G. Washington to James Curtis Booth, December 1, 1854 - Washington, J. G. (1854)
J. G. Washington, of the United States Treasury Department, writes to inform James Curtis Booth (1810-1888) that a proof copy of Booth's report has been sent.
Keywords: Booth, James Curtis, 1810-1888; United States. Department of the Treasury; United States Mint; Mint of the United States; Washington, J. G.